EpCAM silencing suppresses aggressive phenotypes and induces partial redifferentiation in anaplastic thyroid cancer cells - Teruo Nakamura; Tomohiro Shibata; Ken-ichi Ito (PLoS ONE, 2026)
Anaplastic thyroid cancer (ATC) is a rare but highly aggressive malignancy with a dismal prognosis. Although recent advances in targeted therapies have modestly improved survival, the molecular mechanisms driving ATC progression remain incompletely elucidated. Epithelial cell adhesion molecule (EpCAM), a multifunctional cell-surface protein, is implicated in proliferation, migration, and stemness in various cancers. However, its role in thyroid cancer progression remains unclear. In this study, we investigated the function of EpCAM in thyroid cancer cell lines of varying differentiation status. EpCAM expression was significantly elevated in ATC cell lines compared with differentiated thyroid cancer (DTC) lines. EpCAM knockdown by siRNA suppressed proliferation, adhesion, motility, and invasion in ATC cells, but had minimal effects on DTC cells. Morphological analyses revealed that EpCAM silencing induced differentiation features, including follicle-like structure formation and increased expression of thyroid differentiation markers such as thyroglobulin and PAX8 in ATC cells. Furthermore, EpCAM inhibition decreased mesenchymal marker expression, reduced filopodia formation, and suppressed extravasation of cancer cells into the lung in an in vivo mouse model. Mechanistically, EpCAM knockdown attenuated epithelial–mesenchymal transition (EMT)-related pathways but did not affect major proliferation signaling cascades in ATC cells. These findings suggest that EpCAM promotes dedifferentiation and metastatic potential in ATC through EMT modulation. Our results provide new insights into the role of EpCAM in thyroid cancer biology and highlight its potential as a therapeutic target in ATC. Further studies are warranted to elucidate the mechanisms linking EpCAM to anaplastic transformation and to explore the therapeutic efficacy of EpCAM-targeting strategies in aggressive thyroid cancers.